Host sunflower-induced silencing of parasitism-related genes confers resistance to invading Orobanche cumana. Issue 2 (19th November 2020) - Jiang, Zhengqiang; Zhao, Qiqi; Bai, Runyao; Yu, Ruonan; Diao, Pengfei; Yan, Ting; Duan, Huimin; Ma, Xuesong; Zhou, Zikai; Fan, Yanyan; Wuriyanghan, Hada
Abstract: Orobanche cumana is a holoparasitic plant that attaches to host–plant roots and seriously reduces the yield of sunflower ( Helianthus annuus L.). Effective control methods are lacking with only a few known sources of genetic resistance. In this study, a seed-soak agroinoculation (SSA) method was established, and recombinant tobacco rattle virus vectors were constructed to express RNA interference (RNAi) inducers to cause virus-induced gene silencing (VIGS) in sunflower. A host target gene HaTubulin was systemically silenced in both leaf and root tissues by the SSA–VIGS approach. Trans-species silencing of O. cumana genes were confirmed for 10 out of 11 target genes with silencing efficiency of 23.43%–92.67%. Knockdown of target OcQR1, OcCKX5, and OcWRI1 genes reduced the haustoria number, and silencing of OcEXPA6 caused further phenotypic abnormalities such as shorter tubercles and necrosis. Overexpression of OcEXPA6 caused retarded root growth in alfalfa ( Medicago sativa ). The results demonstrate that these genes play an important role in the processes of O. cumana parasitism. High-throughput small RNA (sRNA) sequencing and bioinformatics analyses unveiled the distinct features of target gene-derived siRNAs in O. cumana such as siRNA transitivity, strand polarity, hotspot region, and 21/22-nt siRNA predominance, the latter of which was confirmed by Northern blot experiments. The possible RNAi mechanism is also discussed by analyzing RNAi machinery genes in O. cumana . Taken together, we established an efficient host-induced gene silencing technology for both functional genetics studies and potential control of O. cumana . The ease and effectiveness of this strategy could potentially be useful for other species provided they are amenable to SSA. Abstract : Knockdown of several parasitism-related genes endows sunflower with resistance to invading broomrape.